(untitled) (Research, Society and Development, 2022)
Childhood acute lymphoblastic or lymphoblastic leukemia (ALL) is the result of attack on immature type B lymphocytic cells, the result of acquired genetic damage rather than hereditary, occupying first place in the ranking of disease incidence, according to the National Institute of Cancer (INCA). Improvements in study techniques now provide the opportunity to obtain clinically relevant biological information that may explain apparently abnormal responses to treatment. This study aimed to describe useful diagnostic methods for the classification and treatment of acute lymphoblastic leukemia in children and to present the implications of cytomorphology, cytogenetics, immunophenotyping and cytochemical techniques in the diagnosis and prognosis of leukemia. The systematic review for the elaboration of this consensus was preferably based on indexed articles published in the last ten years based on data from PubMed, Scielo, NCBI. With the results, it was possible to verify, in relation to the hemogram, that the global count of leukocytes in ALL in children can be decreased, normal or increased. In myelogram, the diagnosis of ALL in children is confirmed when more than 25% to 30% of the nucleated cells are blasts. Based on the cytochemical stains, ALL is diagnosed when a positive test is obtained for the PAS techniques. Therefore, knowledge of ways to diagnose and classify ALL in children is extremely important for an early diagnosis and, therefore, to promote an effective treatment.